Chronic kidney disease: systemic influence on dentistry and oral manifestations (Research, Society and Development, 2021)
Chronic kidney disease is a disease that has had its prevalence increased in recent years. It is important to remember that patients with chronic kidney disease (CKD) have oral manifestations arising from systemic influence, so the aim of this work is to establish the main oral manifestations that affect patients with chronic renal failure. This is a bibliographic study, basic, with integrative analysis, for which the databases Pubmed, Google Schoolar and Scielo were used, including articles from 2011 to 2021, in addition to classic articles, where the following descriptors were searched: "Dental care"; "Dentistry"; "Chronic renal failure"; "Chronic kidney disease"; "Kidney failure"; "Chronic renal insufficiency", and the Boolean descriptor "AND". The literature has vast information about these oral manifestations that include: dental caries, clinical attachment loss, periodontal disease, fluorosis, dental calculus, dental plaque, peri-radicular inflammation, microbial infection in the root canal system, dysgeusia, uremic breath, xerostomia, enamel hypoplasia, and taste disorders. In view of all this information, it is important to emphasize the importance of the dental surgeon's follow-up and assistance to these patients.